2001
DOI: 10.1067/mhn.2001.117372
|View full text |Cite
|
Sign up to set email alerts
|

Laryngotracheal Reconstruction in Subglottic Stenosis: An Ancient Problem Still Present

Abstract: Subglottic stenosis is still frequent after tracheal intubation, but other causes must be considered. Laryngotracheal reconstruction with thyrotracheal anastomosis with partial cricoid resection was feasible with good results in 91% of the cases with follow-up, but this procedure must be performed by a skilled surgical team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 21 publications
1
23
0
3
Order By: Relevance
“…This result was similar to Ogura et al [16] (82%), Gerwat et al [17] (100%), Pearson et al [18] (95%), Grillo et al [19] (96%), Maddus et al [15] 94%, Pena et al [14] (95%).…”
Section: Airway Outcomesupporting
confidence: 87%
See 1 more Smart Citation
“…This result was similar to Ogura et al [16] (82%), Gerwat et al [17] (100%), Pearson et al [18] (95%), Grillo et al [19] (96%), Maddus et al [15] 94%, Pena et al [14] (95%).…”
Section: Airway Outcomesupporting
confidence: 87%
“…Friedman and Mayer et al [13] reported 96% (25 of 26 patients) success rate by using sternocleidomastoid myoperiosteal fl ap. Pena et al [14] reported 91% (44 of 48) success rate by LTP.…”
Section: Airway Outcomementioning
confidence: 97%
“…Surgical injury to the cricoid as in a tracheotomy and cricothyroidotomy is believed to lead to airway stenosis [5]. Surgeons have therefore been reluctant to directly incise the cricoid -even in its repair.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the most common cause of adult laryngotracheal stenosis is endotracheal intubation. 75,76 The duration of intubation has been found to correlate significantly with the incidence of laryngeal pathologies, including the development of subglottic edema and narrowing when intubation time exceeds 7 d. 16,77 However, Colton House et al 20 demonstrated no significant difference in the development of subglottic edema regardless of duration of intubation or tube size. The presence of comorbidities, such as diabetes mellitus, gastroesophageal reflux, and immunosuppression, have also been shown to predispose patients to develop stenosis.…”
Section: Larynxmentioning
confidence: 99%